อายุของสภาผู้แทนราษฎร ศึกษาเปรียบเทียบระหว่างรัฐธรรมนูญแห่งราชอาณาจักรไทยกับรัฐธรรมนูญแห่งสหรัฐอเมริกา - ปัณณ์ สีมันตธรรมกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The term of the House of Representatives is an important part of elections, reflecting the will of the people through the electoral mechanism. to have representatives of the people come into power and perform duties of the legislative branch at any given time and the age of the House of Representatives is also related to how close they are to the electorate as owners of sovereignty. It also relates to the executive branch, the stability of the executive branch in the politics of parliamentary countries. The current term of the House of Representatives in Thailand, as stipulated in the constitution, reflects the term of the House of Representatives without citizen participation. Determining the period of time that makes the representatives lose contact with the people and cause various problems. To find a solution to that problem, the authors conducted a study on the age limits of the United States House of Representatives, and the study found that determining the age of the House of Representatives by involving citizens from the very beginning and taking into account the close contact with the people, which is a democratic form of people participating in politics very much This allows people to exercise the right to vote for representatives more often as they wish. and includes a mechanism to control the operations of the government through elections. The author therefore proposes to apply the United States-style prescription of the House of Representatives to Thailand by amending the Constitution of the Kingdom of Thailand. in order to truly reflect democracy with people participation and focus on reflecting and solving problems in a timely manner.